Study on Improving Liquid Carrying Performance of Horizontal Wells With Swirl Jet Composite Device - Huizhen Liang; Lin Mu; Jinyong Li; Chengzhen Li; Jian Ma (Energy Science & Engineering, 2025)
ABSTRACT In the later stages of horizontal gas well development, due to insufficient formation energy, the stratified flow of gas and liquid in the horizontal section generates a decrease in the well's liquid‐carrying capacity, accumulating liquid in the wellbore. Since the flow pattern of gas–liquid two‐phase flow in horizontal wells is significantly different from that in vertical wells, existing vertical well liquid removal and gas production technologies cannot be directly applied to address the liquid accumulation issues in horizontal wells. This paper presents a swirl jet composite device that, through the combination of a spiral guide belt and an internal flow channel, effectively integrates the jet and vortex effects, capable of transforming the stratified flow in the horizontal section into an annular flow, thereby enhancing the gas well's liquid‐carrying capacity. This study applies a combination of theoretical, experimental, and simulation methods to conduct computational fluid dynamics analysis on the device's ability to improve the gas well's liquid‐carrying capacity. It deeply investigates the flow characteristics of the gas–liquid two‐phase flow within the device. The results indicate that the device can not only achieve gas–liquid separation by transforming the flow regime from laminar to an orderly annular flow but also increase the axial velocity to extend the effective distance of the swirling section. Compared with the case without the device installed, the liquid phase volume fraction at the bottom of the well is reduced by 85.9%, and the liquid holdup is reduced by 38%. This demonstrates that compared to traditional technologies such as gas‐lift dewatering and gas production, the device can enhance the liquid‐carrying capacity of horizontal wells and effectively address the issue of liquid accumulation in horizontal wells. It provides theoretical guidance and a practical basis for future research on applying swirl jet composite devices to improve the liquid‐carrying capacity of horizontal wells.